AN OVERVIEW ON POLYCYSTIC OVARIAN SYNDROME - Yedulapuram, Sri Harika; Gunda, Mounika; Moola, Neethika Reddy; Kadarla, Rohith Kumar (Asian Journal of Pharmaceutical Research and Development, 2019)
World Health Organization (WHO) estimates that PCOS has affected 116 million women (3.4%) worldwide in 2012 . Globally, prevalence estimates of PCOS are highly variable, ranging from 2.2% to as high as 26%. In India, experts claim 10% of the women to be affected by PCOS and yet no proper published statistical data on the prevalence of PCOS in India is available. Polycystic Ovary Syndrome (PCOS) is an endocrine metabolic disorder characterized by multiple hormonal imbalances representing diverse clinical presentations dominated by clinical and biochemical signs of hyperandrogenism which results in short and long term consequences in female health. A defect of the ovarian cells (most likely theca cells) is the underlying cause of PCOS, resulting in excessive androgen synthesis and the clinical and biochemical symptoms of the disease. In the literature, reference is made to the participation of genetic factors, including ethnicity; there is a higher frequency of PCOS in Spanish, Native American and Mexican women. The patient seeks a dermatology consultation for one or more complaints like acne, hirsutism, alopecia, acanthosis nigricans, skin tags and occasionally, darkening of complexion with weight gain. . If irregular menstrual cycles or primary infertility are the main complaints, the patient may consult a gynaecologist. Polycystic ovaries found on ultrasound scanning will often have no clinical effects, but PCOS is the most common diagnosis made in women presenting with amenorrhoea, oligomenorrhoea or heavy, irregular and prolonged periods. It is the commonest cause of hirsutism and of infertility due to anovulation. Women with PCOS have increased concentrations of circulating androgens and there is a marked association with insulin resistance, dyslipidaemia, obesity, gestational diabetes, type 2 diabetes and heart disease